Dynamic vapor microextraction of ignitable liquid from casework containers. (July 2022) - Berry, Jennifer L.; Gregg, Mary E.; Friss, Adam J.; Koepke, Amanda A.; Suiter, Christopher L.; Newman, Reta; Harries, Megan E.; Jeerage, Kavita M.
Abstract: Dynamic vapor microextraction (DVME) is a headspace concentration method that can be used to collect ignitable liquid (IL) from fire debris onto chilled adsorbent capillaries. Unlike passive headspace concentration onto activated carbon strips (ACSs) that must be eluted with a toxic solvent (carbon disulfide), DVME employs a relatively benign solvent (acetone) to recover the adsorbed IL residue, and each headspace collection is monitored for breakthrough. Here, for the first time, we extend DVME to casework containers while exploring a realistic range of oven temperatures and collection volumes. We investigated metal cans sealed with friction lids (container 1), metal cans sealed within polymer bags (container 2), and glass jars sealed with two-piece lids (container 3). Without additional containment, container 1 was found to leak so excessively that flow through the capillary was unreliable. Therefore, for containers 2 and 3 only, we determined the total number of target compounds collected from 50% weathered gasoline for oven temperatures from 54 °C to 96 °C and collection volumes from 47 standard cubic centimeters (scc) to 90 scc. Only high-volatility species with retention times (tR )< n -decane on a non-polar column were recovered from polymer bags, whereas headspace concentration from glass jars led to the recovery of target compounds across the entire volatility range. DVME at 90 °C from 2-mL containers showed that the presence of polymer bag material leads to IL vapor losses, particularly for low-volatility species with tR > n -decane. DVME was strongly influenced by the casework container, whereas oven temperature and collection volume had a minor influence for the IL samples explored here. Highlights: Dynamic vapor microextraction (DVME) is a low flow headspace concentration method. DVME cannot be implemented with metal cans with friction lids due to leaks. DVME recovered more target compounds from glass jars than polymer evidence bags. Polymer bag material led to vapor loss, particularly for low-volatility species.